Pelatihan Peningkatan Kapasitas Sumber Daya Manusia UMKM di Masa Pandemi Covid-19 - Raihan Wishal Nafis (Abdi Panca Marga, 2021)
This community service through the Webinar on Increasing the Capacity of Human Resources on Micro Small Enterprise during the Covid-19 Pandemic, the growth of Micro Small Enterprise in Indonesia is increasing over time. So as to be able to maintain the stability of the Indonesian economy. However, the Covid-19 Pandemic has had a very broad impact, starting from the world of education to the business world. One of them is affected in the field of business. Micro Small Enterprises itself is the first step in stabilizing the people's economy. Therefore, in the implementation of this activity, targets that are considered strategic in carrying out training activities to increase the capacity of human resources are participants who have a Micro Small Enterprise to fit their goals, so that they can be implemented efficiently and effectively. Through this community service activity, it is hoped that they will be able to provide solutions so that they can solve the problems described above. The stages of the approach used are, 1) planning stage, 2) preparation stage, 3) implementation phase, 4) evaluation stage. Keywords: Human Resources, Micro Small Enterprise, Covid-19